America's Arab refugees : vulnerability and health on the margins - Inhorn, Marcia C., 1957- (Stanford University Press, 2018)
"America's Arab Refugees is a timely examination of the world's worst refugee crisis since World War II. Tracing the history of Middle Eastern wars - especially the U.S. military interventions in Iraq and Afghanistan - to the current refugee crisis, Marcia C. Inhorn examines how refugees fare once resettled in America. In the U.S., Arabs are challenged by discrimination, poverty, and various forms of vulnerability. Inhorn shines a spotlight on the plight of resettled Arab refugees in the ethnic enclave community of "Arab Detroit," Michigan. Sharing in the poverty of Detroit's Black communities, Arab refugees struggle to find employment and to rebuild their lives. Iraqi and Lebanese refugees who have fled from war zones also face several serious health challenges. Uncovering the depths of these challenges, Inhorn's ethnography follows refugees in Detroit suffering reproductive health problems requiring in vitro fertilization (IVF). Without money to afford costly IVF services, Arab refugee couples are caught in a state of "reproductive exile"--Unable to return to war-torn countries with shattered healthcare systems, but unable to access affordable IVF services in America. America's Arab Refugees questions America's responsibility for, and commitment to, Arab refugees, mounting a powerful call to end the violence in the Middle East, assist war orphans and uprooted families, take better care of Arab refugees in this country, and provide them with equitable and affordable healthcare services."--Amazon.com.